OBSESI TOKOH DALAM NOVEL GURU AINI KARYA ANDREA HIRATA SERTA RELEVANSINYA DALAM PEMBELAJARAN SASTRA DI SMA (TINJAUAN PSIKOLOGI SASTRA) - Senta Manita Br Ginting; Misnawati Misnawati; Indra Perdana; Putri Handayani; Lutfi Aji T (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
This study aims to (1) describe the obsession of the characters in the novel Guru Aini by Andrea Hirata, (2) describe the inner conflicts experienced by the characters in the novel Guru Aini by Andrea Hirata, (3) describe the relevance of the obsession of the characters in the novel Guru Aini by Andrea Hirata in literature learning in high school. The method used in the research is a qualitative description method. The data in this study were sentences, dialogues, and paragraphs in the novel Guru Aini by Andrea Hirata. The data source in this research is the novel Guru Aini by Andrea Hirata published in February 2021 published by PT Bentang Pustaka with a total of 336 pages. The data collection technique is done by using the library / reading technique, taking notes, and then entering it into the data collection table. Data analysis techniques used data reduction, data exposure, and inference. The validity of the data was obtained through source triangulation. The results of this study indicate that (1) the obsession of the characters in the novel Guru Aini by Andrea Hirata, there are four characters who have an obsession, Desi is one of the characters who has an obsession with Desi's obsession, which is obsessed with finding students who are geniuses in mathematics in Ketumbi's village. (2) inner conflict in the novel Guru Aini by Andrea Hirata, there are ten characters who have inner conflicts, Desi is a character who often experiences inner conflicts. (3) the relevance or relevance of the novel Guru Aini by Andrea Hirata in learning literature in class XII high school with basic competencies. 3.3 Analyzing fiction in novels.